The global burden of stroke attributable to high alcohol use from 1990 to 2021: An analysis for the global burden of disease study 2021 - Nannan Qian; Chengcheng Lu; Taohua Wei; Wenming Yang; Hui Han; Meixia Wang; Qiao Shi; Yulong Yang; Hu Xi; Wei He (PLoS ONE, 2025)
Background Stroke, a leading global cause of death and disability, has high alcohol consumption as a significant modifiable risk factor. Despite the known association, the global spatiotemporal burden and changing relationship between high alcohol use and stroke subtypes remain inadequately characterized. This study quantifies the global, regional, and national burden of stroke attributable to high alcohol intake from 1990 to 2021. Methods Utilizing data from the Global Burden of Disease (GBD) 2021 study, we analyzed deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) for stroke attributable to high alcohol use. Metrics were age-standardized rates and stratified by sex, age, sociodemographic index (SDI), GBD region, and stroke subtype (ischemic stroke, intracerebral hemorrhage). Estimated annual percentage change (EAPC) quantified trends. Frontier analysis, decomposition analysis, and cross-country inequality analysis assessed socioeconomic disparities. Results Globally, ASMR decreased by 40.28% (from 7.20 [95% UI 1.40–14.66] to 4.30 [1.00–8.39] per 100,000, EAPC = −1.81) and ASDR declined from 154.83 [33.98–299.48] to 97.89 [23.83–187.71] per 100,000 (EAPC = −1.63). While age-standardized YLL rates markedly improved (EAPC = −1.75), age-standardized YLD rates declined minimally (EAPC = −0.25), indicating persistent long-term disability burden. Significant disparities existed: males consistently bore a higher burden than females, though female ASMR declined more significantly (55.86% vs. 34.25%). High SDI regions showed substantial declines (e.g., ASMR EAPC = −3.28), but low-middle SDI regions experienced increasing ASMR (EAPC = 0.37) and ASDR (EAPC = 0.43), driven by rising YLDs and YLLs. Southeast Asia had the largest ASMR increase (EAPC = 2.86). National burdens were highest in Bulgaria, North Macedonia, and Vietnam. Ischemic stroke burden showed reducing socioeconomic inequality, but intracerebral hemorrhage burden increasingly concentrated in disadvantaged populations (SII = −47.40, CII = −0.19 in 2021). Frontier analysis identified Vietnam, Bulgaria, and Laos with the largest unrealized health potential. Decomposition revealed global DALYs increases were driven by population aging (92.5%) and growth (149.3%), partially offset by reduced age-specific rates (−141.8%). Conclusion Global stroke mortality attributable to high alcohol use declined significantly from 1990 to 2021, reflecting progress in prevention and acute care. However, minimal improvement in disability burden reveals critical gaps in long-term management and rehabilitation, creating a “survival-disability paradox.” Profound disparities persist across genders, regions, SDI levels, and stroke subtypes. Targeted policies addressing excessive alcohol consumption, tailored to regional contexts and focused on both prevention and comprehensive post-stroke care, are urgently needed, particularly in low-middle SDI regions and Southeast Asia, to mitigate disability and health inequities.